Optimizing Breast Cancer Management (Cancer Treatment and Research,, 2018)
This book presents expert opinions on a variety of key topics related to the management of breast cancer, with a focus on the implications of recent advances and research findings for clinical practice. It also explores the controversy regarding mammography screening and reviews the contribution of new imaging modalities. Considerable attention is paid to developments in surgical procedures, including the potential for the safe and effective use of sentinel lymph node dissection alone-even in patients with positive nodes-and to the advantages and contraindications of new radiotherapy techniques. Genetic aspects are discussed in detail, including an assessment of the role of genetic testing and the potential impact of genetic signatures on breast cancer management. New systemic strategies, such as anti-HER2 therapy, endocrine agents, and agents to reverse endocrine resistance, are considered, and the optimal use of chemotherapy for early-stage and advanced-stage disease is addressed. In closing, the book shares important new insights into lifestyle risk factors, risk reduction strategies, and survivor issues, including sexual dysfunction and fertility maintenance.